Resistant Hypertension: Risk Factors, Subclinical Atherosclerosis, and Comorbidities Among Adults—The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - Lotufo, Paulo A. (2015)
Universidade de São Paulo. Centro de Pesquisa Clínica e Epidemiológica. São Paulo, SP, Brasil.